External Switching Dynamics of Optical Bistability System Simulation - Khidhir, Ali Hassan (Iraqi Journal of Science, 2020)
In this work, the external switching dynamics of a Fabry-Perot etalon are studied via optical bistability system simulation. The simulated set-up of this investigation consists of two laser beams; the first beam is continuous (CW) which is considered as a biasing beam and capable of holding the bistable system for a certain range, which we are interested in, from a point that is very close self-switching to a point where the switching is unachievable. The second beam is modulated by passing the first beam through an acousto-optic modulator (AOM) to produce pulses with a minimum rise time and is used as an external source (coherent switching). In this work, we obtained the optical bistable loops by applying absorption coefficient (Î±) = 20cm-1, e sample etalon thickness (D) = 110Î¼m, forward mirror reflectivity (Rf) = 0.6, and backward mirror reflectivity (Rb) = 0.95. The steady state characteristic of an initial detuning of the cavity (Ï†0) = 0.8 was studied at the conditions of no external input pulse intensity (M(t) = 0) and switching that takes place at Is(ON)= 0.57mW and Is(OFF) = 0.4mW.